Improvement in risk prediction for patients with atrial fibrillation and intermediate-risk CHA2DS2-VASc score utilizing highly sensitive cardiac troponin T - Salbach, Christian; Yildirim, Mustafa; Milles, Barbara Ruth; Hund, Hauke; Müller-Hennessen, Matthias; Frey, Norbert; Katus, Hugo; Giannitsis, Evangelos (PLOS ONE, 2025)
Background Guidelines of the European Society of Cardiology recommend a clinical risk assessment for patients with atrial fibrillation (AF). However, scores such as the CHA2DS2-VASc score show only a modest performance for prediction of adverse endpoints. Methods This retrospective single-center all-comer study uses data from the Heidelberg Registry of Atrial Fibrillation of 9,995 patients with non-valvular AF presenting to the emergency department (ED) of the University Hospital of Heidelberg from June 2009 until March 2020. Per CHA2DS2-VASc, risk was classified as low (0 point in men, ≤ 1 point in females), intermediate, or high (≥2 points in men and ≥3 points in females). The predictive performance of the CHA2DS2-VASc score, with and without highly sensitive cardiac troponin T (hs-cTnT), was evaluated for a composite endpoint comprising stroke, myocardial infarction (MI) or all-cause mortality. Results Performance of the CHA2DS2-VASc score for the prediction of the composite endpoint was poor Area under the curve (AUC): 0.648 (95%CI: 0.638-0.657) particularly in patients at intermediate-risk AUC: 0.542 (95%CI: 0.508-0.575). Adding hs-cTnT improved discrimination substantially in intermediate-risk patients (AUC: 0.778, 95% CI: 0.748-0.805). Notably, no events occurred in intermediate-risk patients with undetectable hs-cTnT (<5 ng/L). Conclusion In patients with AF at intermediate thromboembolic risk, the addition of hs-cTnT to the CHA₂DS₂-VASc score enhances prediction of adverse cardiovascular outcomes. Hs-cTnT may help identify patients who could benefit from anticoagulation, while also identifying a low-risk subgroup unlikely to experience events.
Gesehen am 30.01.2026
Im Titel ist "2" tiefgestellt